PROGRAM "LOMBOK RAWIT" SEBAGAI SARANA TERAPI BAGI ANAK TUNALARAS - A.V, Exwan; Rivai, Akhmad; Putri, Riska; Tungung, Niwang (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Student Creativity Program of "Lombok Rawit" standing for Latihan Among Bekso dan Karawitan (practicing dancing and playing gamelan) is motivated by a will to make the traditional Javanese gamelan music and dance as a means of therapy for mentally retarded students. Through this program, the mentally retarded children are expected to be familiar with the Javanese culture, while getting a therapy to reduce emotional and behavioral deviations. This program is implemented to the mentally retarded children in Special School E Prayuwana Yogyakarta. There are 25 students in the school. The training was conducted from April to July, 2014. The results achieved after the training are (1) the increase of the value of the post-test is by 68%. This percentage is obtained from the tabulated results from the instrument, which show a reduction in the number of occurrences. The characteristics of mentally retarded children are hyperactivity, fear, antisocial, etc. (2) The team of this program manage to hold a simple form of collaborative performances of gamelan and dance by the children. (3) The team also manage to compile teaching materials in the form of modules and CD of gamelan and dance lessons for children so that it can be used widely by teachers and therapists of mentally retarded children. Based on the results of the program, it can be concluded that the training of "Rawit Lombok" can be used as a therapeutic tool for such children. Based on the effectiveness of this program, the team of the program try to do a follow up in the form of mentoring and socialization, so that a similar program can be applied to other mentally retarded children in other schools.